Tyrosine Kinases and Phosphatases: Enablers of the Porphyromonas gingivalis Lifestyle - Richard J. Lamont; Daniel P. Miller (Frontiers Media S.A., 2022)
Tyrosine phosphorylation modifies the functionality of bacterial proteins and forms the basis of a versatile and tunable signal transduction system. The integrated action of tyrosine kinases and phosphatases controls bacterial processes important for metabolism and virulence. Porphyromonas gingivalis, a keystone pathogen in periodontal disease, possesses an extensive phosphotyrosine signaling network. The phosphorylation reaction is catalyzed by a bacterial tyrosine (BY) kinase, Ptk1, and a Ubiquitous bacterial Kinase UbK1. Dephosphorylation is mediated by a low-molecular-weight phosphatase, Ltp1 and a polymerase and histidinol phosphatase, Php1. Phosphotyrosine signaling controls exopolysaccharide production, gingipain activity, oxidative stress responses and synergistic community development with Streptococcus gordonii. Additionally, Ltp1 is secreted extracellularly and can be delivered inside gingival epithelial cells where it can override host cell signaling and readjust cellular physiology. The landscape of coordinated tyrosine kinase and phosphatase activity thus underlies the adaptive responses of P. gingivalis to both the polymicrobial environment of bacterial communities and the intracellular environment of gingival epithelial cells.